SPE Latin American and Caribbean Petroleum Engineering Conference 2010
DOI: 10.2118/139339-ms
|View full text |Cite
|
Sign up to set email alerts
|

First Retrievable Directional Casing While Drilling (DCwD) Application in Peruvian Fields Generates Time Reduction and Improves Drilling Performance Preventing Potential Non-Planned Downtime

Abstract: Drilling Operations in Peruvian Jungle requires a complex logistical preparation similar to an offshore project. This high logistic cost that is necessary to drill in this area means a big investment and strongly impacts the daily drilling cost. To minimize potential non productive time (NPT), potential problems that were identified in offset wells (borehole instability, gumbo shales, stuck pipe, etc.), and to improve the drilling performance, Perenco Peru Limited decided to use Directional Casing while Drilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Several examples from applications around the world include Canadian arctic permafrost by Vrielink et al (2008), Lobo field in south Texas by Fontenot (2003), in Brazil by Placido et al (2005 and, Mississippi Canyon by Rosenberg and Gala (2012), in Peruvian Jungle by Beaumont et al (2010), in Saudi Arabia by Chima et al (2012), in Gabon by Askew et al (2011), in San Juan basin by Robinson et al (2008), and finally in Oman by Sanchez et al (2012). The theory behind the field observations has not been fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…Several examples from applications around the world include Canadian arctic permafrost by Vrielink et al (2008), Lobo field in south Texas by Fontenot (2003), in Brazil by Placido et al (2005 and, Mississippi Canyon by Rosenberg and Gala (2012), in Peruvian Jungle by Beaumont et al (2010), in Saudi Arabia by Chima et al (2012), in Gabon by Askew et al (2011), in San Juan basin by Robinson et al (2008), and finally in Oman by Sanchez et al (2012). The theory behind the field observations has not been fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…The DCwD response is not significant dissimilar than the regular approach when conventional drilling is used (Beaumont et al, 2010), but requires additional equipment for tripping out and in with a specific set of running tools (to retrieve or set a new BHA). Under this circumstance (casing string on slips and drillpipe inside with running tools), there are two different flow paths from where the well can take an influx:…”
Section: Well Controlmentioning
confidence: 99%
“…The Casing Drilling application was able to meet the planned objectives of drilling the shallow hole sections in a total loss scenario uneventfully", (Gallardo et al 2010). Beaumont et al (2010) reported another successful Casing Drilling application in Peruvian fields. "The main problem in this area was time-consuming gumbo events in the intermediate hole.…”
Section: Casing/liner Drilling Successful Case Studiesmentioning
confidence: 99%
“…Severe drag and tight spots led to high risk trips out-ofhole requiring extensive back-reaming and near-lost hole events in offset wells (severe pack-offs while tripping out). Potential problems associated with hole instability, clay swelling, stuck pipe, hole cleaning, gumbo, surface equipment downtime and seepage losses were entirely mitigated with Casing Drilling application", (Beaumont et al 2010). Torsvoll et al (2010) have done a case study on the successful application of Liner Drilling technology in Norwegian Continental Shelf (NCS) where many fields have formation instability and/or depletion history.…”
Section: Casing/liner Drilling Successful Case Studiesmentioning
confidence: 99%